Modeling the temporal effects of external trade components of Kenya on the balance of trade (BOT) - Ndiga, Njeru Dominic (Meru: Dominic Ndwiga Njeru, 2014)
The project aimed to assess the exports and imports variables that significantly determine the balance of trade for Kenya over the period of time. In addition it sought to model the balance of trade on the context of exports and imports. The methodology used was Principle Components Analysis and time series. The study through principle components analysis, led to determing the mojor exports and imports variables. time series analysis on the othe hand comprises methods for analysing time series data in order to extract meaningful statistics and other characteristics of the data and time series forecasting. Deficit in Kenya's balance of trade could lead to high inflation rate which leads to a general rise in the prices of services and goods.
A Research Project Submitted in the Partial Fulfillment for the Award of Masters of Science Degree in Applied Statistics in the School of Pure and Applied Sciences of Meru University of Science and Technology.